Leveduras produtoras de AIA e solubilizadoras de P visando a promoção de crescimento de tomateiro - Oliveira, Thaís Borges de (2016)
Microorganisms Plant Growth Promoters (MPCV) have the ability to produce compounds which stimulate plant growth by different mechanisms, such as the production of plant hormones and solubilization of minerals. Considering these aspects, this study aimed to evaluate the potential of yeast strains as plant growth promoters by producing indole acetic acid (IAA) and phosphate solubilization, and its inoculation of tomato seedlings. Six yeast strains were evaluated belonging to bank microorganisms Agricultural Microbiology and Molecular Laboratory (LAMAM - CCA, UFSCar). For the evaluation of IAA production by isolates the colorimetric method was used, modified DiMenna (1957); for quantification of tricalcium phosphate solubilization was used to colorimetric method of molybdenum blue. The test with tomato seedlings was conducted in a greenhouse with different cell concentrations of T. globosa (5S55) and with or without addition of glucose and tryptophan. The results showed that isolates of T. globosa and Rh. mucilaginosa produced IAA in the presence of tryptophan; the isolates of T. globosa and M. guilliermondii solubilized inorganic phosphate in a liquid medium. The isolate T. globosa (5S55) promoted the growth of tomato seedlings, with significant increases in the length of shoot and root. In conclusion, the isolates of T. globosa, Rh. mucilaginosa and M. guilliermondii have the potential for improving plant production by IAA production and / or phosphate solubilization; the yeast T. globosa (5S55) was shown to promote growth of tomato plants.